2016
DOI: 10.1093/nar/gkw817
|View full text |Cite
|
Sign up to set email alerts
|

The PathoYeastract database: an information system for the analysis of gene and genomic transcription regulation in pathogenic yeasts

Abstract: We present the PATHOgenic YEAst Search for Transcriptional Regulators And Consensus Tracking (PathoYeastract - http://pathoyeastract.org) database, a tool for the analysis and prediction of transcription regulatory associations at the gene and genomic levels in the pathogenic yeasts Candida albicans and C. glabrata. Upon data retrieval from hundreds of publications, followed by curation, the database currently includes 28 000 unique documented regulatory associations between transcription factors (TF) and targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Considering an at least 1.5-fold difference in protein expression activation in wild-type vs. Δ cgpdr1 cells exposed to 5-flucytosine, nine proteins were found to be repressed by CgPdr1; while eight proteins were found to be activated by CgPdr1 (Table 1). The PDRE loci BCCRYYRGD, TCCRYGGA (Tsai et al, 2010), TCCACGGA, and HYCCGTGGR (Paul et al, 2014), were searched for in the promoters of the referred genes using the PathoYeastract database (Monteiro et al, 2016). Interestingly, considering these 17 proteins, at least one CgPdr1-binding site is found in the promoter regions of nine genes, suggesting the action of CgPdr1 in their expression may be direct.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering an at least 1.5-fold difference in protein expression activation in wild-type vs. Δ cgpdr1 cells exposed to 5-flucytosine, nine proteins were found to be repressed by CgPdr1; while eight proteins were found to be activated by CgPdr1 (Table 1). The PDRE loci BCCRYYRGD, TCCRYGGA (Tsai et al, 2010), TCCACGGA, and HYCCGTGGR (Paul et al, 2014), were searched for in the promoters of the referred genes using the PathoYeastract database (Monteiro et al, 2016). Interestingly, considering these 17 proteins, at least one CgPdr1-binding site is found in the promoter regions of nine genes, suggesting the action of CgPdr1 in their expression may be direct.…”
Section: Resultsmentioning
confidence: 99%
“…Using the PathoYeastract database (http://pathoyeastract.org/cglabrata/index.php Monteiro et al, 2016), it is possible to verify that the CgFLR1 was found to be up-regulated upon the over-expression of CgPdr1, in control conditions (Noble et al, 2013), or upon benomyl or selenite exposure, in the dependency of CgYap1 (Chen et al, 2007; Lelandais et al, 2008; Merhej et al, 2016). Additionally, CgFLR1 expression was shown to be repressed by the transcription factor Stb5, a negative regulator of azole resistance in C. glabrata (Noble et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 33% of the genes up-regulated in the acidic biofilms are documented targets of Ndt80 transcription factor, 32% of Efg1, 16% of Bcr1, 13% of Tec1 and 13% of Brg1 (S2 Table). Figure 3 shows the target genes of Efg1, Brg1, Bcr1 and Tec1 with differential expression under biofilm-forming conditions, according with the information available on the PathoYeastract database [36]. A significant overlap between the genes regulated by each transcription factor was observed, confirming the complex and intertwined nature of the regulatory network controlling expression of biofilm genes in C. albicans [31].…”
Section: Resultsmentioning
confidence: 95%
“…To further understand the transcriptional regulatory network active in the formation of biofilms under acidic conditions we used the PathoYeastract database [36] to cluster the up-regulated genes with transcription factors reported to control the process of biofilm formation in C. albicans (Ndt80, Efg1, Bcr1 and Tec1) [31]. Approximately 33% of the genes up-regulated in the acidic biofilms are documented targets of Ndt80 transcription factor, 32% of Efg1, 16% of Bcr1, 13% of Tec1 and 13% of Brg1 (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation